precariat - Grigoryeva, Elena (project baikal, 2018)
The topic of the current issue is one of the most complicated and contentious issues of our uneasy time. The emergence of a new class called precariats has been identified just recently: this new term was introduced by G. Stending from Great Britain seven years ago. He called the new class currently emerging and bearing a huge devastating potential “precariat” (similar to “proletariat”, from Latin precarium – unreliable, unstable).The tangle of problems united by the term “precariat” includes economics, robotics, sociology and demography. It embraces the problem of migrants flooding rich countries, as well as an ominous question: where to place people who no longer have an opportunity to work in industry or services? The prospects of space development of Russia and the imperial approach. Renovation (reanimation?) of small cities, which found themselves in precarious situation. In Russia, the future gets an additional charge of uncertainty because the strategies of its geopolitical development are ambiguous.Triggered by the challenges of the new millennium, the processes generally called “precariat” are complicated and diverse. We have tried to do a review of opinions and thoughts on this subject expressed by different people – scientists, architectural theoreticians and renowned architectural practitioners.